Professores e outros agentes educacionais: de leitores à co-a(u)tores de pesquisa - de Souza Bezerra, Daniella; Furquim, Alex; Morais, Edivania; Gouveia, Liderzí; Serravalli, Vitor; Assis, Talline (Domínios de Lingu@gem, 2012)
Resenha